DWT 2019
DOI: 10.5004/dwt.2019.23992
|View full text |Cite
|
Sign up to set email alerts
|

Assessing willingness to pay for upgrading toilets in rural areas of Shaanxi and Inner Mongolia, China

Abstract: Unsanitary toilets are recognized worldwide as a threat to ground water and public health. In this research, we investigated villagers' willingness to pay to upgrade toilets in Shaanxi and Inner Mongolia. The study was based on data from 558 questionnaires collected in December 2017 and January 2018. The villages and villagers were randomly chosen. We observed that 42% of the respondents were willing to pay to upgrade toilets, and the key factors that affected willingness were dissemination, concern, gender, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Review literature reveals several factors influencing household WTP for improved sanitation services: age, sex, education level, household size, wealth index, etc. 15 - 22 , 33 Are the WTP-associated factors observed in other contexts similar to those recorded in the Beninese context?…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Review literature reveals several factors influencing household WTP for improved sanitation services: age, sex, education level, household size, wealth index, etc. 15 - 22 , 33 Are the WTP-associated factors observed in other contexts similar to those recorded in the Beninese context?…”
Section: Discussionmentioning
confidence: 91%
“…Similar to the present study, several authors have adopted a dichotomous approach with some variations. 16 , 17 , 19 , 22 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with households that had not performed any renovations a relatively larger proportion of households that had recently renovated their toilets expressed willingness to invest more than CNY 2000 in further renovations. A previous survey found that mean willingness to pay for toilets among rural households was USD 73 (CNY 525) in the Inner Mongolia region and USD 64 (CNY 460) in Shaanxi province (Wu et al, 2019).…”
Section: Household Attitudes To the Toilet Revolutionmentioning
confidence: 99%
“…Poor sanitation around the world results in increased prevalence of disease and increased environmental pollution 8,9 . Unsanitary toilets are recognized worldwide as a threat to ground water and public health 10 . Previous studies have confirmed that poor toilet conditions are linked to increased prevalence of diarrhea 11 , and that household access to improved toilets is often associated with reduced stunting risk 12 .…”
Section: Introductionmentioning
confidence: 99%